The incidences of and consultation rate for lower extremity complaints in general practice. Issue 6 (3rd November 2005) - van der Waal, J M; Bot, S D M; Terwee, C B; van der Windt, D A W M; Schellevis, F G; Bouter, L M; Dekker, J
Abstract : Objective: To estimate the incidence and consultation rate of lower extremity complaints in general practice. Methods: Data were obtained from the Second Dutch National Survey of General Practice, in which 195 general practitioners (GPs) in 104 practices recorded all contacts with patients during 12 consecutive months in computerised patient records. GPs classified the symptoms and diagnosis for each patient at each consultation according to the International Classification of Primary Care (ICPC). Incidence densities and consultation rates for different complaints were calculated. Results: During the registration period 63.2 GP consultations per 1000 person-years were attributable to a new complaint of the lower extremities. Highest incidence densities were seen for knee complaints: 21.4 per 1000 person-years for women and 22.8 per 1000 person-years for men. The incidence of most lower extremity complaints was higher for women than for men and higher in older age. Conclusions: Both incidences of and consultation rates for lower extremity complaints are substantial in general practice. This implies a considerable impact on the workload of the GP.